An Engineered Patient‐Derived Tumor Organoid Model That Can Be Disassembled to Study Cellular Responses in a Graded 3D Microenvironment. (5th August 2021) - Landon‐Brace, Natalie; Cadavid, Jose L.; Latour, Simon; Co, Ileana L.; Rodenhizer, Darren; Li, Nancy T.; Wu, Nila C.; Bugbee, Eryn; Chebotarev, Aleks; Zhang, Ji; Wouters, Bradly G.; McGuigan, Alison P.
Abstract: Patient‐derived organoids (PDOs) are emerging as powerful models to capture the genetic heterogeneity of human tumors. However, the self‐assembling nature of PDOs limits their use in studies of the impact of microenvironmental heterogeneity on tumor cell function. Here, a paper‐based model, the Tissue Roll for Analysis of Cellular Environment and Response (TRACER) is adapted, using patterned polymer infiltration, to enable controlled assembly and disassembly of organoid structures to study the impact of both genetic and microenvironmental heterogeneity on tumor cell behavior. In the adapted platform (TRACER2), pancreatic cancer PDOs establish oxygen gradients across the tissue and in response exhibit graded cell viability, proliferation, hypoxia‐response gene transcription, and response to gemcitabine therapy. Further, PDOs retrieved from the hypoxic regions of the TRACER2 cultures show graded transcriptional changes in immunosuppression‐related genes and upon co‐culture, after TRACER2 disassembly, induce graded functional changes in Jurkat cells and macrophage cells. Therefore, TRACER2 offers a novel platform to dissect the effects of microenvironmental parameters on tumor cell function. Abstract : This paper describes the design and validation of a 3D culture platform—Tissue Roll for Analysis of Cellular Environment and Response (TRACER2)—that enables controlled assembly/disassembly of patient‐derived organoid cultures to create graded tumor microenvironments with representative genetic heterogeneity. TRACER2 recapitulates known tumor biology and offers a unique platform to examine microenvironmental impacts on tumor cell function and behavior.